Основні тенденції розвитку геоінформаційних навігаційних систем прецизійного землеробства в Україні - Касім, М. М.; Васюхін, М. І. (Енергетика і автоматика, 2017)
MaIN trends in geographic informationAL navigation SYSTEMS OF PRECISION AGRICULTURE IN UKRAINE M. Кasim, M. Vasyuhin The results of research on the influence of application of geographic informational navigation system of precision agriculture on environmental, economical, time and technical factors for the development of agriculture in Ukraine are described. It allowed identifying a number of disadvantages of the existing systems in this class, among which the main ones are binding of subject information primarily not to the maps, and to the schematic maps and the lack of domestic tools that provide the required precision of positioning of moving objects.It was found that the agroecological monitoring plays a role of the feedback to regulate the situation in the agricultural sector because the development of the concept an effective monitoring system based on GIS and remote sensing is an important task and implies, in turn, to develop the conceptual approaches to current, accurate and rapid monitoring .Precision agriculture contains a lot of elements that can be divided into three main tasks, execution each of which requires appropriate specialized technical hardware and software: the collecting information about farm, field, cultures; the analysis of the collected information and the decision, which consists in carrying out technological operation.The navigation subsystem which installed on agricultural machinery includes a global positioning system (GPS / GLONASS) – receiver, board computer, software. This complex allows recording the coordinates for the current unit, height and other parameters to any desired intervals. This record of navigation content held in well-known formats ESRI Shapefile and Mapinfo, allowing to import them in office GIS for further processing and perform the necessary calculations.It is shown that the differential GPS measurements to be more accurate than usual. This caused by that the reference station with known coordinates calculates the amendments and transmits the combined message for correcting the satellite measurements. These messages can take any number of slave GPS receivers to eliminate almost all errors in their measurements.The primary issue is the development of algorithm for determining the precise location of mobile objects of ground, air and space basing, involved in the implementation of precision agriculture technology. This algorithm associated with the explanation of choosing a way of increasing the accuracy of positioning objects: DGPS (Differential Global Positioning System), RTK (Real Time Kinematic), VRS (Virtual Reference Station), RTX (Real Time eXtended).Outlined in this paper approaches create conditions for improving the status and sustainability of agricultural sector towards the information quality management, innovation and attraction of investments and so on. Their implementation requires extensive research and development of application software and hardware systems for testing in a particular farm.